PERAN KELOMPOK USAHA BERSAMA (KUBE) CITRA MANDIRI DALAM PEMBERDAYAAN PENGRAJIN INDUSTRI KREATIF DI DESA PUCANG KECAMATAN SECANG KABUPATEN MAGELANG - Shakuntala .; Suwanto Adhi; Wiwik Widayati (Journal of Politic and Government Studies, 2015)
Creative economic players in Indonesia need to be empowered because a creative economy now plays a major role in improving the welfare of society. This empowerment can be done by existing business group in the area. Joint venture group (KUBE) Citra Mandiri is one group that was formed to empower the craftsmen creative industries in the Pucang village Secang District of Magelang regency. But after KUBE Citra Mandiri established Pucang rural welfare still increasing because they found the poor and the vulnerable poor and unemployed.By this research, the writer wants to explain the role of the joint venture (KUBE) Citra Mandiri in empowering craftsmen creative industries and factors that constrain KUBE Citra Mandiri in empowering craftsmen creative industries in the Pucang village Secang district of Magelang regency.By using interviews and observations in research methods, the writer found that the role of the joint venture (KUBE) Citra Mandiri in empowering craftsmen creative industries is not maximum. The writer also found that the factors that constrain KUBE Citra Mandiri in empowering craftsmen creative industries is organizational / institutional, human resources officials and the general public, and group management.Keywords : Creative Industries Pucang Village, KUBE Citra Mandiri, Craftsman Empowerment